PENGEMBANGAN SISTEM MONITORING MY SCHOOL DENGAN MENGGUNAKAN NETBEANS - Trista, Riezca Talita; Wisdariah, Wisdariah (Jurnal Manajamen Informatika Jayakarta, 2021)
The development of the My School monitoring system aims to provide a more efficient managerial solution in managing student data and school activities. This system is designed to simplify the process of monitoring attendance, academic assessments, and other activity reports. In its development, the Integrated Development Environment (IDE) NetBeans is used, offering comprehensive features to support the development of desktop and web-based applications. The methodology used in this system development is the SDLC-based software development model, which involves the stages of analysis, design, implementation, and system testing. The results of this study indicate that the developed system can enhance the efficiency of data management and monitoring processes at schools, while providing easy access for stakeholders, such as teachers, school principals, and parents.